GEOTOURISM POTENTIALS OF GEOSITES IN DURRËS MUNICIPALITY, ALBANIA - Braholli, Ermiona; Menkshi, Edlira (Quaestiones Geographicae, 2021)
Present geological and geomorphological objects are non-living features that can enhance curiosity and increase the knowledge of Earth’s history, through the development of geotourism. The municipality of Durrës, located in western Albania represents an active tectonic area with numerous landforms, an evidence of geodiversity and geoheritage. In this paper, the most typical geosites are identified mainly based on their scientific values as well as their geotourism potential. After the defining of 5 geosites, through geological and topographical map, we applied the Geosite assessment model (GAM). GAM is widely used in Europe on different areas and has given good results in the evaluation of geosites. The GAM method involves only experts’ opinions, which are essential for the preliminary development of geotourism in Albania. This method produce different main values (MV) and additional values (AV) score, which are very useful results in preservation, conservation and promotion of the area.